2019
DOI: 10.3390/jmse7090307
|View full text |Cite
|
Sign up to set email alerts
|

Critical Processes of Trace Metals Mobility in Transitional Waters: Implications from the Remote, Antinioti Lagoon, Corfu Island, Greece

Abstract: The Antinioti Lagoon is a karstified, rather pristine, and shallow coastal lagoon located in the northern part of Corfu Island in NW Greece. The present study examines the levels of metals (Al, Fe, Mn, Cd, Cu, Pb, and Zn) in the dissolved and particulate phase, as well as in surface and core sediments, and identifies the critical processes that define their behavior. The major transport pathway of dissolved Mn, Cd, and Pb, and particulate Mn, Cd, and Zn into the lagoon is through freshwater springs, whereas su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Botsou et al [12] analyzed the aspects related to metals' mobility in the water column, focusing their attention on Antinioti Lagoon and Corfu Island. In particular, they investigated the processes responsible for the mobility of metals both in and beyond the transitional fresh-saline water interface.…”
Section: Papers Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Botsou et al [12] analyzed the aspects related to metals' mobility in the water column, focusing their attention on Antinioti Lagoon and Corfu Island. In particular, they investigated the processes responsible for the mobility of metals both in and beyond the transitional fresh-saline water interface.…”
Section: Papers Detailsmentioning
confidence: 99%
“…The issue collected five papers that cover different aspects of coastal and ocean engineering, chemical oceanography, geology, and geomorphology using different approaches and instruments. Some of the studies used numerical models [10,11], others acquired and analyzed field data regarding chemical [12] or geomorphological aspects of the ocean [13] while Lisi et al [14] suggested a mathematical modeling framework to analyze the effects of sediment handling operations.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-increasing attention paid by researchers from diverse research fields to TW is primarily related to the inclusion of TW into the regulations imposed by the WFD on the EU Member States with regard to a good ecological status, its criteria, and its indicators [15]. The majority of papers on these issues have been published by authors from Mediterranean countries, i.e., Italy [16][17][18], Greece [19][20][21], and Spain [22][23][24] in particular. The investigated and assessed good ecological status indicators range from invertebrates [25][26][27] to fish [28][29][30] and aquatic macrophytes [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Deltas of large rivers and adjacent coastal areas are transitional environments, where parameters of the media and element mobility change significantly at rather short distances, and interactions between fluvial and marine processes significantly affect their geochemistry (Dada et al, 2016;Botsou et al, 2019). Chemical and physical gradients typical for such systems lead to the partial removal of both suspended and dissolved matter, which sequentially results in the formation of barrier zones (Chen et al, 2020;Savenko and Pokrovsky, 2020).…”
Section: Introductionmentioning
confidence: 99%